Application of two‐dimensional gel‐based mass spectrometry to functionally dissect resistance to targeted cancer therapy. Issue 11 (December 2013) - Klein, Oliver; Rohwer, Nadine; de, Katja Freitag; Mergler, Stefan; Wessendorf, Petra; Herrmann, Marion; Klose, Joachim; Cramer, Thorsten; Sauer, Sascha
<x xml:space="preserve">Abstract</x> Purpose The majority of gastric cancers are diagnosed at advanced stages, characterized by robust therapy resistance. The oncoprotein hypoxia‐inducible factor 1 (HIF‐1) is associated with therapy resistance, partly via activation of the DNA damage response. We have noted a robust ability of gastric cancer cells to functionally compensate the loss of HIF‐1 in vitro. The purpose of this study was to identify molecular pathways that underlie this compensation. Experimental design We performed 2DE to compare the nuclear proteome of wild‐type and HIF‐1‐deficient gastric cancer cells. Differently expressed protein spots were identified via MS). After bioinformatic evaluation, functional validation of selected identified pathways was performed. Results 2DE displayed a total of 2523 protein spots, from which 87 were identified as regulated by HIF‐1. Seventy of the identified spots were different proteins and 17 were isoforms. Bioinformatic analyses revealed that a significant amount of the identified proteins were related to cellular survival pathways. Specifically, members of the proteasome pathway were found upregulated upon loss of HIF‐1. Combined inhibition of HIF‐1 and the proteasome inflicted significant DNA damage, supporting the hypothesis that the proteasome is of functional importance to compensate the loss of HIF‐1. Conclusions and clinical relevance Our data show robust and functional changes of the nuclear proteome upon inactivation of the HIF‐1 oncoprotein in gastric cancer cells. We propose that 2DE‐MS represents a useful tool to functionally dissect resistance mechanisms to targeted therapy and to identify novel targets for antiproliferative combination therapy.